Los costos del crimen en Uruguay - Diego Aboal; Jorge Campanella; Bibiana Lanzilotta (Inter-American Development Bank (IDB), 2013)
– This paper uses cost accounting to estimate some of the costs associated with criminal activity and violence in Uruguay. Among the costs being considered are those of security and crime prevention; justice; incarceration and rehabilitation of prisoners; stolen goods; health care and loss of life resulting from violence; and costs associated with prisoners' loss of productive time while in prison. A variety of methodologies and sources of information were utilized to calculate these cost estimates. Although a significant range of costs has been covered, the cost of crime as a whole has not been accounted for due to limited information. Consequently, cost estimates must be interpreted as a minimum benchmark. The total estimated cost for 2010 in Uruguay comes to 3. 1 percent of gross domestic product (GDP).
Keywords: D60; H50; I31; K14; 330